Diverse Exotic Orders and Fermiology in Fe-Based Superconductors: A Unified Mechanism for B1g/B2g Nematicity in FeSe/(Cs,Rb)Fe2As2 and Smectic Order in BaFe2As2 - Onari, Seiichiro; Kontani, Hiroshi (Frontiers in Physics, 2022)
A rich variety of nematic/smectic orders in Fe-based superconductors is an important unsolved problem in strongly correlated electron systems. A unified understanding of these orders has been investigated for the last decade. In this article, we explain the B_1g symmetry nematic transition in FeSe_1-xTe_x, the B_2g symmetry nematicity in AFe_2As_2 (A=Cs, Rb), and the smectic state in BaFe_2As_2 based on the same framework. We investigate the quantum interference mechanism between spin fluctuations by developing the density wave equation. The observed rich variety of nematic/smectic orders is naturally understood in this mechanism. The nematic/smectic orders depend on the characteristic shape and topology of the Fermi surface (FS) of each compound. (i) In FeSe_1-xTe_x (n_d=6.0), each FS is very small and the d_xy-orbital hole pocket is below the Fermi level. In this case, the small spin fluctuations on three d_xz, d_yz, and d_xy orbitals cooperatively lead to the B_1g nematic (=0) order without magnetization. The experimental Lifshitz transition below the nematic transition temperature (T_S) is naturally reproduced. (ii) In BaFe_2As_2 (n_d=6.0), the d_xy-orbital hole pocket emerges around M point, and each FS is relatively large. The strong spin fluctuations due to the d_xy-orbital nesting give rise to the B_1g nematic (=0) order and the smectic [=(0,π)] order, and the latter transition temperature (T^*170K) exceeds the former one (T_S140K). (iii) In heavily hole-doped AFe_2As_2 (n_d=5.5), the large d_xy-orbital hole pocket and the four tiny Dirac pockets appear due to the hole-doping. The B_2g nematic bond order emerges on the d_xy-orbital hole pocket due to the same interference mechanism. The present paramagnon interference mechanism provides a unified explanation of why the variety of nematic/smectic orders in Fe-based superconductors is so rich, based on the well-established fermiology of Fe-based superconductors.